An Integrative Teaching Factory-Industry Model To Improve Communication Skills And Employability Skills Of Vocational High School Students - Eka Saraswati; Nurul Astuty Yensy B; Sudarwan Danim (DAWUH : Islamic Communication Journal, 2025)
Vocational high schools are expected to supply work-ready graduates, yet many programmes still struggle to translate technical competence into workplace performance, especially in communication-intensive tasks such as customer needs analysis, teamwork coordination, reporting, and quality-related documentation. Teaching Factory (TeFa) has been promoted in Indonesia as a production-based learning approach that simulates or delivers real industry orders within a school environment. However, TeFa initiatives frequently prioritise output volume and technical procedures, while employability skills are treated as implicit by-products rather than explicit learning targets that are taught, practiced, and assessed. This article proposes an Integrative Teaching Factory-Industry Model (iTeFIM) that embeds structured communication and employability competencies into the end-to-end TeFa production/service cycle, supported by governance, industry partnership mechanisms, and competency-based assessment. Using an integrative literature review, policy analysis, and design-synthesis methods, we develop a logic model, implementation roadmap, and assessment toolkit aligning (i) work-based learning principles, (ii) employability competency rubrics, and (iii) Indonesian vocational governance and TeFa policy directions. The model positions communication as a core operational capability across six learning-production stages: order intake, planning, execution, quality assurance, delivery, and after-sales reflection. We discuss design implications for school-industry collaboration, teacher and instructor roles, learning analytics, and continuous improvement using CIPP-informed monitoring. The article contributes a practical, assessment-ready framework that can be adapted across vocational programmes to strengthen graduates’ readiness for employment and career mobility